Upaya Peningkatan Kualitas Pelayanaan Sarana dan Prasarana Pendidikan di Tkk St. Michael Baobolak - Olgaviani C.Namu; Maria D. Kono; Mikael M.K. Sare; Yohanes B. Siki; Sisilia E. Lidyawati; Indriyati Indriyati; Maria Florencia Yunita Bello (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
The program of efforts to improve the quality of educational facilities and infrastructure services at TKK St. Michael Baobolak, the development of economic literacy in the Maryke Village community aims to improve the quality of educational services at TK St. Michael Baobolak through the provision of facilities and infrastructure that are still inadequate, such as teaching aids, reading books, and play equipment. Thus, it is expected to create a more conducive and enjoyable learning environment for children, and support their optimal growth and development. This study uses a qualitative approach with a descriptive method. Data were collected through direct observation, interviews with related parties such as the principal, teachers, and staff, as well as documentation related to educational facilities and infrastructure at TKK St. Michael Baobolak. The results of the study showed that this program succeeded in improving the quality of educational facilities and infrastructure services at TKK St. Michael Baobolak. On the other hand, the results of this activity have also provided coloring tools and alphabet posters. Coloring tools, such as crayons, colored pencils, and markers, are very important media to stimulate children's creativity. Through coloring activities, children not only train their fine motor skills, but also develop their imagination and ability to express themselves. Meanwhile, alphabet posters serve as effective visual aids to help children recognize letters and build the foundations of reading skills, thus having a positive impact on their well-being.